Aristotle on the Philosophical Nature of Poetry. The Object of Mimesis According to Poet. 9 - Schütrumpf, Eckart E. (Hyperboreus, 2015)
In Rep. book 10 Plato had assigned to the whole of mimesis and speciﬁcally to poetry a place three removed from truth and inferior than the reality of human affairs. By contrast, Aristotle in Poet. ch. 9 declared poetry to be more philosophical than historiography, that is superior to the description of men’s interactions. How does Aristotle achieve this new and positive assessment of poetry? Instead of taking objects by themselves and placing them into a vertical hierarchy according to their ontological rank as model and imitations on different levels, Aristotle views literature under the aspect of the stringency of the causal connection of events with one another or the connection of actions with the character that produces them. This causal relationship can be of the weaker form of likelihood or the strong form of necessity. Likelihood corresponds to the form of exactness which according to Nic. Eth. 1 the philosophical discourse on issues that occur in a speciﬁc way at best most of the time, like those which form the subject of ethics, allows. The other possibility of poetical presentation, necessity, transcends the conditions of practical philosophy and meets the standard of science. In tragedy the poet construes the plot according to these principles of universality, and comes closer to philosophy than a description of factual events is. It is possible that the expression of this standard of poetic presentation in Poet. ch. 9 is owed to Plato’s Theaetetus.